Emha Ainun Najib and Sufism Communication: Congregation of Maiyah Kenduri Cinta as Case Study - Khoiro, Dela Amaliya; Hermansah, Tantan; Rizky, Kiky (UIN Fatmawati Sukarno Bengkulu, 2022)
This study answers questions about Sufism as a communication message for Emha Ainun Nadjib in the Ma'iyah Kenduri Cinta discussion group at Taman Ismail Marzuqi, Central Jakarta. This study uses a descriptive qualitative approach using data collection techniques: observation, interviews, and documentation. The theoretical basis uses narrative theory. Then the result is obtained. First, Emha Ainun Najib is a literary figure, more inclined to Sufism using Sufism literature when communicating with the congregation. Second, Emha Ainun Najib is a Sufi poet who is not much different from Sufi poets such as Rabi'ah Al-Adawiyah, Ibn Arabi, Al-Hallaj, and Rumi. However, they are already included in the category of a Sufi, while Emha is still not at that stage. Third, Emha Ainun Najib, during his lecture, conveyed his religious experience through literature: form of Sufistic poetry, without letting go of the pure nature of God, who is One, transcendent, and immanent. Fourth, Emha Ainun Najib is a character or lecturer who can demonstrate coherence in conveying his messages of Sufistic value to the Ma'iyah congregation of love celebrations and Emha when conveying his ideas, and thoughts through the Sinau Together approach (lectures & joint discussions). In addition, through the CakNun.com youtube media, books and poetry.